Discourse and language use in history-taking stage of veterinarian-client-patient interaction - Jamal, Noorjan Hussein (2020)
Human and veterinary medical consultation consists of similar phases. Medical consultation phases, including history taking, involve several activities. These activities of informing, complaining, advicegiving, describing, requesting, apologizing, joking, greeting, and others, are organized events. Activities of each stage of the medical consultation, either human or veterinary, have unique tasks and goals. For example, the history-taking stage in veterinarian-client-patient interaction is an activity of a series of requests, answers, reactives, advice giving and so on. The veterinarian’s goal is to collect comprehensive information about the animal’s health problem. The clients’ task is to help their veterinarians arrive at an accurate diagnosis by providing them with relevant and complete information about their animals’ health problem. This can be achieved by the use of proper language expressed by the performance of different discourse strategies, communicative acts, questions, and interactional features. This study aims to describe the overall structure of veterinarian-client-patient interaction during the history-taking stage, examine the communicative acts employed by the veterinarians and the clients, determine the types, forms, and functions of questions used by the veterinarians to solicit information from the clients, identify the interactional features and their functions used in veterinarian-client-patient talk, and finally explore how all these discourse features contribute to framing the relationship between the veterinarians and their clients.The data were collected by means of audio, video recordings and field observation notes from a public veterinary clinic in Malaysia. For data analysis, a discourse and speech act analysis were used to qualitatively and quantitatively analyse the data. The findings showed the largest amount of consultation concentrated on seeking and providing information by the veterinarians to the clients using different discourse strategies and communicative acts. Veterinarians also tended to build a relationship and rapport with the clients using various interactional features of talk such as the use of: simple and informal language, facilitative response remarks, generic vocabulary among others. Moreover, the veterinarians controlled the amount and type of gathered information through dominating the questions speech act. Clients also interacted with the veterinarians by asking questions and providing information important for diagnosing their pet animals’ health problem. The results of the study provide some insights for trainee veterinarians and scholars on how interactional strategies facilitate soliciting clients’ concerns and arrive at accurate diagnoses.